Wire bonding on glass substrates via vapour deposition of Ag-Ti film. (August 2019) - Kam, Nicholas; Hook, Michael David; Tang, Tanya; Mayer, Michael
Abstract: Circuits on glass technology have recently developed in applications such as interposers, fibre optics, and displays. We report an automatable method towards interconnecting to glass circuits via wire bonding with maintained transparency. The method is based on wire bonding Au-Ag, using 25 μm diameter 99.99% pure Au wire. A 5 nm Ti and 500 nm Ag base film are initially deposited via e-beam evaporation onto a standard glass slide, where after wire bonding is preformed. The metal film is then etched from the substrate via ion-milling; remaining intact only in areas shielded from the beam. Cross-sections of the bonded balls before and after metallization removal show high quality continuous interfaces with no intermetallic or micro void formations. Good reliability was indicated by shear testing, remaining above 100 MPa for at least 8 days of ageing at 200 °C. Strong wire bonds were thus obtained on a glass substrate by deposition and selective removal of a Ag-Ti film.